Implementation of Parenting Programs in the Covid-19 Era in Online Learning for Early Childhood - Muhamad Iand Aditya Nugroho; Imam Shofwan (Genius Journals, 2021)
The era of the COVID-19 pandemic is happening in all corners of the world and has a major impact on all areas of human life. All sectors including Indonesia are affected, including the education sector. Problems in the learning process in the pandemic period require all elements of education to form learning that adapts to the environment and conditions that arise. The purpose of this study is to describe the application of parenting plans along with supporting factors and obstacles to RA Hidayatul MubtadiIen in learning online in the COVID19 pandemic.
Keywords: Parenting Program; Early Childhood; Covid-19; corners